Texturing absence: a geography of the disappeared Woodstock Beach - Anderson, Molly (Environmental Humanities South, 2023)
Up until the late 1960s, the Cape Town suburb of Woodstock had a beach. Decades of land reclamation – begun as early as 1890 – culminated in the beach being entirely subsumed by railways, roads, and harbor infrastructure. Woodstock's beachside heritage is largely unknown, as are the processes by which it disappeared, meaning that its role as a site of shipwrecks, a source of food, and a place of leisure has long gone unexplored and unacknowledged. What does the presence, and then absence, of Woodstock Beach mean for people and place in Cape Town? Understanding the role of Woodstock Beach in the making of the city requires a methodological approach that is attuned to both presence and absence. The method of ‘texture' draws on creative and critical approaches to trace the beach through material inscriptions, memories, metaphors, archives and histories. Texture offers an extended rigor by engaging ambiguities, absences, glimpses, and incoherent strands as generative moments that allow more traces to be followed. This critical and creative orientation is engaged in the analysis and the writing of these stories. Attending to Woodstock Beach in this way reveals a series of small-scale and intimate stories about everyday people and things, which layer and juxtapose with stories of slavery, dispossession, colonialism, capitalism, and apartheid. The stories of Woodstock Beach – its presence and its disappearance – illuminate continuities and connections across place, time, and scale which highlight the nuanced, complicated, and always ongoing ways in which place and its politics are made and re-made both in Cape Town, and at a countrywide scale.